(untitled) (International Journal of Business, Economics and Management, 2023)
The years 2020 and 2021 were not easy for the world’s population, as the COVID-19 pandemic compromised all countries and created restrictions never imagined by people and highlighted the use of digital technologies. One of the areas that has evolved a lot is Distance Learning with the help of digital platforms, therefore, this article aims to verify how distance learning with the use of digital platforms has created value from the perspective of users during the COVID-19 pandemic. In this research, it was decided to use the qualitative and quantitative methodological procedure through a questionnaire with eleven questions and to analyze the data obtained in the field research, the concept of value was used based on the definitions of Priem (2007). The survey data were collected from April 4 to 21, 2021, using Google forms and the sample obtained 286 observations and eleven variables. From the proposed study, it is clear that the objective of this research was achieved, based on the analysis of the four categories presented in the results and analysis section, we were able to prove that distance education through digital platforms generates value that is perceived by the respondents.